Does Educational Background Matter? The Role of Competency Alignment in Learning Outcomes among Fashion Education Students - Laila Hanifah; Wulansari Prasetyaningtyas (Jurnal Penelitian Pendidikan, 2026)
Students entering vocational higher education often have different secondary educational backgrounds, which are commonly assumed to influence their academic achievement. This study examined whether educational background affects learning outcomes when students learn competencies that are relatively new to all learners. A quantitative causal-comparative (ex post facto) design was employed involving 83 undergraduate students enrolled in the Fashion Education Study Program who had completed the Fabric Construction Techniques course. Participants were classified into graduates of SMK Fashion (n = 32) and graduates of senior high schools (SMA) or non-fashion vocational high schools (n = 51). Learning outcomes were analysed using descriptive statistics and an independent-samples t-test. Students from SMK Fashion achieved a slightly higher mean score than the comparison group (83.47 vs. 82.45), but the difference was not statistically significant, t(81) = 0.793, p = .430, with a small effect size (d = 0.18). These findings indicate that secondary educational background explained little variation in learning outcomes. The study suggests that academic performance in vocational higher education depends less on school type than on the alignment between prior learning experiences and university competencies. The findings highlight competency alignment as an important explanation of learning outcomes in vocational higher education.